A companion to the Spanish Renaissance - Kallendorf, Hilaire (Renaissance Society of America series., 2019)
A renewed case for the inclusion of Spain within broader European Renaissance movements. This interdisciplinary volume offers a snapshot of the best new work being done in this area.